Torch War Tradition in Jepara District, Central Java (The Study of Living Quran Q.S. Al-Baqarah 152) - Irwansyah, Muhammad; Fatah, Abdul (Tebuireng: Journal of Islamic Studies and Society, 2024)
This study aims to understand more deeply the meaning of the torch war tradition in Tegal Sambi Village, Tahunan Subdistrict, Jepara Regency in the perspective of Q.S. Al-Baqarah/2: 152. The method of study is a qualitative through a phenomenological approach, the data of this study are obtained from observations, interviews, documentation, journal articles, books, tafsir books, and similar literature to explain the history of the Torch War tradition. The results of this study found that the symbolic meaning of the torch war is closely related to gratitude for the gifts of Allah SWT, in the form of crops and the sea. The local community connects this tradition with the content of Q.S. Al-Baqarah/2: 152, which shows the harmony between cultural practices and the Qur'an. In the torch war there are several symbols, the symbol of fire is interpreted as a cleanser of negative energy. The light of the torch as a symbol of illuminating the darkness with knowledge. The hard and dry coconut fronds symbolize strength and resilience. Dry banana leaves that are flammable and produce thick smoke symbolize fertility and purity. The relevance of the torch war culture with Q.S. Al-Baqarah/2:152 is that the torch war reflects human efforts to get closer to Allah, be grateful for His blessings, and cleanse themselves of all impurities of the heart.